College student-athletes' COVID-19 worry and psychological distress differed by gender, race, and exposure to COVID-19-related events - Moore, E. W. G.; Petrie, T. A.; Slavin, L. E. (Journal of Adolescent Health, 2020)
Purpose: The purpose of this study was to determine the prevalence of National Collegiate Athletic Association (NCAA) student-athletes` exposure to COVID-19-related events (e.g., canceled season, diagnosed with COVID) and their psychological distress in April/May 2020. Methods: The link to the online survey was emailed to NCAA student-athletes by the NCAA Student Athlete Advisory Council and the athletic departments of 80 NCAA institutions. In April-May of 2020, student-athletes (N = 5915; women = 3924) completed the online survey once. The survey included measures of their psychological distress, COVID-19 worry, and their exposure to different COVID-19-related events. To examine differences in exposure to COVID-related events by racial, ethnicity, and gender identities, we conducted logistic regressions. A path analysis examined relationships between COVID-related events, COVID-19 worry, and psychological distress for men and women. Results: Student-athletes` exposure to COVID-19 events differed significantly by gender, race, and ethnicity. In addition, 58.7% of women's and 54.5% of men's psychological distress variance was explained by the path model and mostly by their COVID-related worry. Student-athletes` stress was directly related to the changes that occurred in class delivery (i.e., online format) and indirectly by being quarantined. Men's psychological distress was also related through worry by their sport season being canceled. Discussion: The general uncertainty and worry about COVID individuals experienced at the beginning of this pandemic primarily explained the athletes' high levels of psychological distress. As COVID-19 continues to cause quarantines and changes educational experiences, the worry and psychological distress of college students are likely to continue.